2023
DOI: 10.1039/d2bm01935c
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/PDA@Cu composite as a peroxidase-mimicking enzyme with high-effect antibacterial and anticancer activity

Abstract: Since nanozymes were proposed, their applications have become more and more extensive. As a research hotspot in recent years, MoS2 also shows many enzyme-like properties. However, as a novel peroxidase,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Based on the aforementioned content, we have designed a novel MoS 2 /PDA@Cu nanozyme, 162 as depicted in Fig. 12.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Based on the aforementioned content, we have designed a novel MoS 2 /PDA@Cu nanozyme, 162 as depicted in Fig. 12.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…At present, highly active antibacterial nanomaterials have attracted growing interest as antibacterial agents, including carbon-based nanomaterials, 35-44 noble metal nanomaterials, [45][46][47][48][49][50][51] metal oxide nanomaterials, [52][53][54][55][56][57] transition metal sulfides, [58][59][60] metal-organic frameworks (MOFs) 61,62 as well as composite nanomaterials (Table 1). [63][64][65][66][67][68] The currently studied antibacterial mechanisms mainly involve the following aspects: physical penetration, physical wrapping, photothermal ablation, and oxidative stress (Fig.…”
Section: Antibacterial Mechanisms Of Nanomaterialsmentioning
confidence: 99%
“…Liu et al indicated that the PDA molecule, metal Cu NPs, and Cu 2+ could promote the catalytic reaction of MoS 2 /PDA@Cu nanozyme, and exhibit good inhibition against S. aureus when the concentration was 25 μg mL −1 . 59 In addition, evidence has emerged that H 2 O 2 or O 2 could be adsorbed on the metal surface. It could accomplish the enzymatic activity by decomposition and producing ROS for antibacterial action.…”
Section: Reviewmentioning
confidence: 99%
“…5 Some semi-conductor photocatalysts, such as metal oxides, metal sulfides, carbon-based materials, etc., 6 exhibit high inherent peroxidaselike activity and can efficiently catalyze low-concentration H 2 O 2 to active • OH, which shows higher antibacterial activity than H 2 O 2 . 7 Taken together, the special antibacterial mechanism of semiconductor photocatalyst prevents the development of drug resistance and presents fewer side effects of the photocatalytic inactivation technique.…”
Section: ■ Introductionmentioning
confidence: 99%